Performance of Si-doped TiAlxN supernitride coated carbide tool during dry machining of Inconel 718 superalloy. (December 2022) - Pandey, Kshitij; Datta, Saurav
Abstract: Conventional high speed dry machining using uncoated carbide tool is challenging for machining of difficult-to-cut aerospace superalloy Inconel 718. On the other hand, coolant-assisted machining may not be a feasible solution always due to issues related to operator's safety and environmental protection. Use of harder tool materials is also not wise always in purview of production economics. Application of coated carbide tools is therefore being given importance since last several decades. In this context, present work examines performance of newly developed Si-doped TiAlxN supernitride nanocomposite (HSN2 ) coated carbide tool during dry machining of Inconel 718. Tool performance is assessed in perspectives of a few machinability criteria such as cutting force, tool-tip temperature and width of tool flank wear. Different tool wear mechanisms are explained in correlation with properties of tool substrate and coating material. The work also includes study of chip's micro-morphology. It is experienced that HSN 2 coated tool outperforms uncoated WC-Co tool. As compared to uncoated tool, lower cutting force, reduced tool-tip temperature and shorter width of tool flank wear are obtained during application of HSN 2 coated tool. HSN 2 coated tool produces chips with better underside surface morphology and lower microhardness than its uncoated counterpart. HSN 2 coated tool experiences ~17 % reduced temperature at the tool-tip when compared to uncoated counterpart, operated at cutting velocity = 47 m/min. As compared to uncoated carbide tool, HSN 2 coated tool causes ~56 %, ~ 57 % and ~43 % reduced tangential cutting force, feed force and radial force respectively, at cutting velocity = 134 m/min. Usage of HSN 2 coated tool causes lower flank wear (~ 15 % reduced) than that of uncoated counterpart, operated at the highest cutting speed (134 m/min). Chips evolved by using HSN 2 coated tool corresponds to ~9 % reduced microhardness (within shear band) than that obtained using uncoated tool at cutting velocity = 103 m/min.